Reassessing the conservation outlook for Madagascar’s endemic Anatidae following the creation of new protected areas - Razafindrajao, Felix; Bamford, Andrew J.; Young, H. Glyn; Andrianarimisa, Aristide; Bin Aboudou, Abdallah Iahia; Lewis, Richard E. (Wildfowl, 2017)
Madagascar has three endemic species of Anatidae, all of which are classified by the International Union for Conservation of Nature (IUCN) as Endangered or Critically Endangered. Until recently there have been no protected areas within their ranges to secure key habitat. The creation of several new protected areas in Madagascar since 2010 has created an opportunity for better conservation management of these species, most obviously for Madagascar Pochard Aythya innotata which occurs at just a single site that has now been protected. We created distribution models for the other two species, Madagascar Teal Anas bernieri and Meller’s Duck A. melleri, using survey data collected from 2004–2013 and MaxEnt software. Predicted ranges were compared with the locations of protected areas. Additionally, for each species, population monitoring was carried out at one site at which there has been conservation intervention. Our models predicted that breeding Madagascar Teal would occur near healthy mangroves (family: Rhizophoraceae) in areas with high mean temperature, but the total extent of predicted suitable habitat is just 820 km2. Non-breeding Meller’s Duck favour water surrounded by dense vegetation, in areas with low human population density. Meller’s Duck occurs in at least nine protected areas, but most of these were set up for forest conservation and may not support many individuals. Since 2010, two wetland protected areas that could benefit Meller’s Duck have been created, although one is small and the other, Alaotra, is heavily disturbed. The population of Meller’s Duck at Alaotra is stable. Four new protected areas will benefit Madagascar Teal, covering more than half of the predicted breeding range for this species. The population at one of these protected areas, the Manambolomaty delta, is increasing. Overall, we conclude that the conservation outlook for Madagascar Teal is improving, but the small range for this species means it is dependent on good management at protected areas where it does occur. Meller’s Duck requires more attention, and the outlook for this species remains poor.